Impact of COVID-19 pandemic on the health-related anxiety and behavioral changes among pregnant women – A cross-sectional study - Roy Chowdhury, Ranita; Sarkar, Suvobrata; Pal, Manidip; Mukherjee, Jayeeta; Bera, Gairik (Asian Journal of Medical Sciences, 2021)
Background: The outbreak of COVID-19 has been the cause of agony for millions of people worldwide. Anxiety of losing near ones and stress of rearing children besides bearing the bulk of domestic tasks have led to certain behavioral changes in the pregnant women. Aims and Objectives: This study aims to assess anxiety, awareness, and behavioral changes among pregnant women during COVID-19 pandemic. Materials and Methods: A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, College of Medicine and J.N.M. Hospital, Kalyani, West Bengal, India, from May 1, 2020, to December 31, 2020. All antenatal patients after the second trimester visiting the OPD or maternity ward, satisfying inclusion criteria after formal consent, were considered for the study. Results: Out of a total of 139 patients, mostly primigravida, 122 (87.7%) participants were of 18–33 years age. Observations revealed that 24% more women were worried about their own health after the arrival of pandemic. The overall worry percentage for unborn baby (88%), existing children (76%), and older relatives (38%) remained uniform throughout the study period. Staying at home, stocking of food, and medical equipment showed a downward trend toward the end of the study. Conclusion: The impact of the pandemic has been mammoth, taking a toll on the behavior and anxiety of the pregnant women, which when unnoticed may have a long-term effect on their mental health as well as family life. Physical and mental support from external and internal sources will pave the way to a healthier mental well-being of these antenatal mothers.